Modulation of Microenvironment Signals by Proteolytic Shedding of Cell Surface Extracellular Matrix Receptors - Itoh, Yoshifumi (Frontiers in Cell and Developmental Biology, 2021)
Multicellular organisms are composed of cells and extracellular matrix (ECM). ECM acts as a glue to connect cells, provides scaffolding for migrating cells, and pools cytokines and growth factors. ECM also directly sends signals to the cells through ECM receptors, providing survival signals and migration cues. Altogether, ECM provides a correct microenvironment for the cells to function in the tissue. Although ECM acts as a signaling molecule, unlike soluble factors such as cytokines and growth factors, they are insoluble solid molecules. Upon cell binding to the ECM through ECM receptors and signals transmitted, cells then need to have a mechanism to release from ECM to prevent prolonged signals, which may be tumorigenic, and to migrate on ECM. One of the effective means to release the cells from ECM is to cleave the ECM receptors by proteinases. In this mini-review, current knowledge of ECM receptor shedding will be discussed.